Rancangan Ujian Rating Personel Pemandu Lalu Lintas Penerbangan Berbasis Online di Perum LPPNPI Cabang Denpasar - Syahrial, Irga Tegar; Rany Adiliawijaya Putriekapuja (Jurnal Bisnis dan Operasi Penerbangan, 2024)
In carrying out the task of air traffic service, ATC at Perum LPPNPI Denpasar Branch is required to have a license, rating, and health certificate. The validity period of an ATC rating is 6 (six) months and must be renewed by conducting a rating exam again. Currently at Perum LPNPI Denpasar Branch, the rating exam for ATC personnel is still carried out offline which requires a lot of time and preparation. This research was conducted with the aim of designing an online-based rating exam website for ATC personnel at Perum LPPNPI Denapasar Branch. The research method used is research and development.